The Implementation of Find Someone Who Games on the Students Speaking Ability - Eka Susilawati (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study aims to investigate the impact of implementing Find Someone Who games on the speaking ability of students in the 8A class of SMP IT Al Izzah Sorong. The research employed a Classroom Action Research (CAR) design to observe the effectiveness of using interactive and engaging language learning activities in improving students' speaking skills. The participants of the study were 30 eighth-grade students from 8A class who were involved in the Find Someone Who games during English language lessons. The research was conducted over a period of six weeks, with data collected through speaking assessments, observations, and student feedback. The findings of the study revealed a significant improvement in the students' speaking ability after the implementation of Find Someone Who games. It can be seen from the pretest mean score was 70.58. In cycle one posttest, the score improved becoming 78.67 and in cycle two posttest become 82.45. The interactive nature of the games encouraged students to engage in meaningful conversations, practice speaking in English, and build confidence in expressing themselves orally. The results suggest that incorporating interactive language learning activities such as Find Someone Who games can be an effective strategy to enhance students' speaking skills in the language classroom.